“Perhaps we should exchange some ideas on the subject”: the journey of a sociologist, woven between (self)reflection and dialogue - Monteiro, Alcides (Adult Education Discourses, 2024)
“Where, therefore, do you come from, as a researcher?” Faced with this question, which is part of the invitation to write this text, I answer: I’m a sociologist. From this intellectual background, I construct my autobiographical narrative, where I give particular importance to the way in which my contact with this science permeates the academic field in which I practise my profession, and the intellectual field in which I do research. But I also define myself as a civically committed sociologist because I refuse to stay on the side of the road, just observing social reality. I believe I have a duty to help transform society into a better place to live. My identification with a “sociology of action” comes from multiple influences, which I try to portray here. This text is also a tribute of recognition and gratitude to some of the persons who have populated my intellectual landscape, many of whom are still there. They range from authors I’ve never met in person, but have read with the greatest interest, to author-friends with whom I’ve had the pleasure of exchanging enriching conversations and ideas.